Dynamics of bacterial abundance and the related environmental factors in large shallow eutrophic Lake Taihu. Issue 1 (1st January 2017) - Gong, Yi; Tang, Xiangming; Shao, Keqiang; Hu, Yang; Gao, Guang
ABSTRACT: In aquatic ecosystems, estimation of bacterial abundance (BA) is intimately connected to the development of an understanding of the role of bacteria in microbial food webs. Flow cytometry (FC) can rapidly calculate BA, but to date mostly has been applied in marine waters with limited use in shallow eutrophic lakes because of the abundant organic and inorganic matter. To seek the best compromise between precision and the clarity for the differentiation of bacteria from other submicron-sized particles and colloids in eutrophic lakes, we optimized FC instrument settings, fixatives and storage conditions, ultrasonic pre-treatment and staining protocols. Then, BA in Lake Taihu was investigated by the optimized FC procedures. Regression analysis showed good correspondence ( R 2 = 0.72, p < 0.001, n = 128) of BA counted by FC and epifluorescence microscopy. The developed protocol was successfully applied to monitor the dynamics of BA in the large shallow eutrophic Lake Taihu. A distinct spatio-temporal shift of BA in Lake Taihu was observed. The shift was found to be mainly related to dissolved organic carbon, total suspended solids, water temperature and chlorophyll- a . Our results highlight the effect of sediment re-suspension and algal biomass on BA in eutrophic shallow lakes.